(untitled) (Journal Of Educational and Psychological Researches, 2014)
Chapter One First, the importance of research and the need for him Highlight the status of the nation and occupies a decent position among nations by what they offer for the good of humanity and tender, which is based mainly on the human and material wealth owned by the nation. The investment of this wealth investment scientifically accurate based on the strong foundation that qualifies them to heights of glory, so stand out necessary development of all energies Alepeshriaaly the limit can not be considered as these energies fortune unless all elements of effective elements characterized by the positive interaction in various spheres of life and in the introduction that the young to enjoy its capabilities and preparations were produced by the nature of their stage age . That phenomena and problems among the students of the university are many and varied vary according to individual circumstances and different psychological, social, economic and environmental. The overseas students living in a new community, so feel more conflict because of the lifestyles, habits and values ​​different from their environment, of whom suffer alienation and homesickness and friends and family and the difficulty in harmony with the new life and instability as well as "on the perception of inferiority to the Arabs and the problems of accommodation and housing and the difficulties of learning the language and others . Second: Find the limits Current search is determined by the Iraqi students studying in Ukrainian universities from all disciplines , universities and both sexes for the academic year ( 2011-2012) Third: Research Goals Current research aims to identify 1_The degree of problems with a sense of Iraqi students studying in Ukrainian universities 2_Detect the significance of differences in the problems of Iraqi students studying in Ukraine according to the variable level of study ( Phase I ) , ( the other stages) 3_Detect the significance of differences in the problems of Iraqi students studying in Ukraine according to the variable competence ( medical colleges ) ( other colleges) 4_Detect the significance of differences in the problems of Iraqi students studying in Ukraine by time spent abroad Problems of students in descending order of " percentile by weight .5_ Chapter II The second chapter First: the theories that dealt with the study of the problems . Psychoanalytic theory.1 . Theory of the self.2 . Social learning theory.3 . Cognitive behavioral theory.4 . Behavioral theory.5 Second, previous studies Chapter III: This chapter includes a presentation "to process pursued by the researcher to achieve the objectives of the research Identify community and style selection of the sample and the number of steps and tool construction and characteristics of standard statistical methods that were used to process the data. Chapter IV The results of research and interpretation Recommendations Proposals The research involved (supplements and sources